Taking exception to the law : materializing injustice in early modern English literature - Beecher, Donald; Wallace, Andrew, 1973-; Williams, Grant, 1965-; DeCook, Travis, 1976- (University of Toronto Press, 2014)
Taking Exception to the Law explores how a range of early modern English writings responded to injustices perpetrated by legal procedures, discourses, and institutions.